A PROPOSED FRAME OF REFERENCE FOR RESEARCH OF SAME-DIFFERENCE IN CROSS-CULTURAL COMMUNICATION AND PRAGMATIC FAILURE IN INTERCULTURAL COMMUNICATION: REFERENCE OF EXPRESSION (CULTURE) - Quang, Nguyen (VNU Journal of Foreign Studies, 2021)
The author of this article proposes a frame of reference for research on same-difference and pragmatic failure in cross-cultural and intercultural communication. This frame is developed with three dimensions of reference: ‘Expression’ (Culture), ‘Impact’ (Communication) and ‘Level’ (Layers of reference). Review of different approaches to the dimension of ‘Expression’ by different scholars, such as Hofstede, Trompenaars and Hampden-Turner, Hall and Lewis is presented with comments before the author’s own is to be given in the next article.